2010
DOI: 10.1146/annurev.economics.102308.124433
|View full text |Cite
|
Sign up to set email alerts
|

Microeconomics of Technology Adoption

Abstract: Differences in technology levels across countries account for a large component of the differences in wages and per-capita GDP across countries worldwide. This article reviews micro studies of the adoption of new technologies and the use of inputs complementary with new technologies to shed light on the barriers to technology diffusion in low-income countries. Among the factors examined affecting decisions pertaining to technology choice and input allocations are the financial and nonfinancial returns to adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
462
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 749 publications
(484 citation statements)
references
References 34 publications
16
462
1
5
Order By: Relevance
“…An increase in the formal education by one year increased the amount of land allocated to seed multiplication by 0.08ha. This is perhaps because education increases the individuals' ability to access and process information and might increase their profits from seed (Teklewold et al, 2006;Foster and Rosenzweig, 2010).…”
Section: Farmers' Participation In Cbsmementioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the formal education by one year increased the amount of land allocated to seed multiplication by 0.08ha. This is perhaps because education increases the individuals' ability to access and process information and might increase their profits from seed (Teklewold et al, 2006;Foster and Rosenzweig, 2010).…”
Section: Farmers' Participation In Cbsmementioning
confidence: 99%
“…In particular, results indicate that when the household landholding increased by one hectare, the probability that the producer would choose the formal sources of bean seed for planting increased by 15.8 percent; while that of choosing informal seed source reduced by 23.1 percent (Table 4). Landholding is a surrogate for risk taking, access to information and credit, all of which are positively associated with adoption of new innovations (Feder et al, 1985;Foster and Rosenzweig, 2010).…”
Section: Farmers' Participation In Cbsmementioning
confidence: 99%
“…The process of technology adoption and diffusion has been shown to be driven by several factors beyond market mechanisms (Foster and Rosenzweig, 2010). Social interaction effects, comprising both peer and network effects, have been found to play a relevant role for the decision to adopt a technology, in several fields such as agriculture, health prevention and financial decisions (Foster and Rosenzweig, 1995;Conley and Udry, 2010;Kremer and Miguel, 2007;Oster and Thornton, 2012;Godlonton and Thornton, 2012;Duflo and Saez, 2003;Beshears et al, 2015;Bursztyn et al, 2014) 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies in economics have shown that both imperfect information and poor institutions impede the adoption of new technologies. In particular, learning about a new crop takes time, and this slows its spread (Foster and Rosenzweig, 2010). Conley and Udry (2010) demonstrate that pineapple farmers in Ghana learn about proper fertilizer use by observing their neighbors' choices and outcomes.…”
Section: Introductionmentioning
confidence: 99%